The Effect of Carbon Performance and Carbon Emission Disclosure on Firm Performance - Angelina Yuvita Todryyanti Mai; Murtanto Murtanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of carbon performance and carbon emission disclosure on firm performance. Firm performance is measured using Return on Assets (ROA), while carbon performance is measured based on carbon intensity. Carbon emission disclosure is measured using a disclosure index referring to the Carbon Disclosure Project (CDP) checklist developed by Choi et al. (2013). This study applies a quantitative approach using secondary data obtained from annual reports and sustainability reports of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2023-2024 period. The sample was selected using a purposive sampling method, resulting in 242 firm-year observations. The data were analyzed using panel data regression with EViews 12. The results show that carbon performance does not have a positive effect on firm performance. In contrast, carbon emission disclosure has a positive and significant effect on firm performance. In addition, leverage as a control variable has a negative and significant effect on firm performance. These findings indicate that corporate transparency in disclosing carbon emission information can strengthen stakeholder trust and support the improvement of firm performance. This study contributes to the development of environmental accounting literature and provides practical implications for companies, investors, and regulators in encouraging more transparent and accountable carbon emission disclosure practices.